Pengaruh Pelaporan Berkelanjutan dan Modal Intelektual Hijau terhadap Nilai Perusahaan dengan Set Kesempatan Investasi sebagai Variabel Pemoderasi - Fransiska Ayu Septhiani; Nera Marinda Machdar (UNIVERSITAS KALBIS, 2022)
This study aims to analyze the effect of sustainability reporting and green intellectual capital on firm value with investment opportunity set as moderating. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2013 - 2018. The sample selection method used purposive sampling method and obtained a total sample of 87 companies or 522 observational data. The author usesthe method of data analysis with 2 regression models, the method is multiple regression analysis and Moderated Regression Analysis (MRA) using version 9 of E-views program. The results of partial testing show that sustainability reporting does positively affect firm value while green intellectual capital has a negative effect on firm value. Besides the other results found in this study, invetment opportunity set does not moderate the relationship between sustainability reporting and firm value, and also investment opportunity does moderate the relationship between green intellectual capital and firm value.